Physiotherapy, movement, and action - Nicholls, David A; Vieira, Adriane (Physiotherapy theory and practice, 2023)
Movement has always been central to physiotherapy practice and theory. But physiotherapists have largely focused on forms of human bodily movement governed by the neuro-mechanical body system in illness or injury. Many other forms of movement exist though, and we argue here that the exploration of these other movements might give physiotherapists new language, concepts, and tools, to guide its adaptation to forms of healthcare that are becoming increasingly complex, diverse, and inclusive. Drawing on Hannah Arendt's concept of vita activa (or "active life"), we examine how physiotherapists have traditionally captured and defined movement. Critiquing past practices for over-emphasizing what Arendt called labor, and work, we suggest that an approach governed by her concept of action, might offer physiotherapists a way to give movement greater significance. We explore what active life might mean for a revised approach to movement, and highlight examples of vita activa already emerging in physiotherapy. We close the paper by calling for a reevaluation of what movement means for the profession and its clients.